Management of right ventricular outfl ow tract obstruction: Evolution to revolution - Gewillig, M.; Brown, S.C. (SA Heart Journal, 2017)
Percutaneous pulmonary valves have opened up new avenues of treatment in patients requiring pulmonary valve replacement. The management of tetralogy of Fallot demonstrated the evolution of treatment: from palliative care to modern day early complete surgical repair. Use of trans-annular patches to treat right ventricle outfl ow obstruction gave rise to signifi cant pulmonary regurgitation. Clinicians considered this a benign condition until, three decades later patients started dying unexpectedly. Surgical pulmonary valve replacement was the only treatment, but these showed dysfunction after some years. Clear guidelines for intervention do not exist. Current guidelines recommend treatment at upper limits of tolerance. Arguments for earlier intervention are presented, but none of the guidelines have been scientifi cally validated.